Law Enforcement of Corruption Crime Abuse of Hospital Medical Devices by State Civil Apparatus - Nurfaizy, Muh. Rafly; Karim, H. M. Said (Law Study Program, Faculty of Law, Nusantara Islamic University, 2023)
The purpose of this research is to (1) determine the Corruption Criminal Law Policy on Hospital Medical Device Misuse by State Civil Apparatuses. (2) The government's role in prosecuting state civil apparatus corruption crimes involving hospital medical device misuse. In this thesis, written using an empirical legal approach, the author examined law in its true sense and how it functions in society. According to the study's findings, the role of criminal law in dealing with criminal acts of corruption committed by the state apparatus in the form of hospital medical device abuse is contained in Articles 8, 9, 10, 11, 12, 12B, and 23 of the Corruption Act. Corruption is a heinous crime committed only by civil servants or state administrators. The role of law enforcement in the enforcement of corruption crimes involving hospital medical device abuse begins with the submission of reports from individuals, community organizations and non-governmental organizations, state institutions and government institutions, and internal police information reports, which is then followed by an investigation process aided by the police and the Attorney General's Office. The public prosecutor decides if the investigator's case file is deemed complete and the case can be prosecuted.Penelitian ini bertujuan untuk, mengetahui Kebijakan Hukum Pidana Korupsi terhadap Penyalahgunaan Alat Kesehatan Rumah Sakit oleh Aparatur Sipil Negara. (2) Peran pemerintah dalam penindakan tindak pidana korupsi penyalahgunaan alat kesehatan rumah sakit oleh aparatur sipil negara. Dalam tesis yang ditulis dengan menggunakan pendekatan hukum empiris ini, penulis mengkaji hukum dalam arti yang sebenarnya dan bagaimana hukum itu berfungsi dalam masyarakat. Berdasarkan hasil penelitian, peran hukum pidana dalam menangani tindak pidana korupsi yang dilakukan oleh aparatur negara dalam bentuk penyalahgunaan alat kesehatan rumah sakit terdapat dalam Pasal 8, 9, 10, 11, 12, 12B, dan 23 Undang-Undang Tindak Pidana Korupsi. Korupsi merupakan kejahatan keji yang hanya dilakukan oleh pegawai negeri atau penyelenggara negara. Peran penegak hukum dalam penegakan tindak pidana korupsi penyalahgunaan alat kesehatan rumah sakit diawali dengan adanya laporan dari perorangan, organisasi masyarakat dan lembaga swadaya masyarakat, lembaga negara dan lembaga pemerintah, dan laporan informasi internal kepolisian, yang kemudian dilanjutkan dengan proses penyidikan yang dibantu oleh pihak kepolisian dan Kejaksaan. Jaksa penuntut umum akan memutuskan apakah berkas perkara dari penyidik sudah dianggap lengkap dan dapat diajukan ke pengadilan.